Angels & demons - Howard, Ron, 1954-; Grazer, Brian, 1953-; Calley, John; Koepp, David; Goldsman, Akiva; Hanks, Tom; McGregor, Ewan, 1971-; Zorer, Ayelet; Skarsgard, Stellan; Favino, Pierfrancesco; Kaas, Nikolaj Lie, 1973-; Mueller-Stahl, Armin, 1930-; et al. (Culver City, California Sony Pictures Home Entertainment, 2009)
Harvard symbologist Robert Langdon discovers evidence of the resurgence of the most powerful underground organization in history, the Illuminati. Upon learning of an unstoppable terrorist act against the Vatican, Langdon travels to Rome and joins forces with Italian scientist Vittoria Vetra, and together they will follow the 400-year-old Path of Illumination that leads to the Vatican's only chance for survival.
Title from container.
Originally produced as a motion picture in 2009.
Based on the novel by Dan Brown.
Widescreen 2.40;1.
Special features: "Rome was not built in a day:" the filmmakers share their secrets to creating the world of Angels & demons; "Writing Angels & demons:" Dan Brown and the screenwriters discuss adapting his best-selling book into a movie; "Characters in search of the true story:" the cast share their experiences of bringing Dan Brown's characters to the screen; "CERN: Pushing the frontiers of knowledge:" a look at one of the world's largest and most respected scientific research centers.
Director of photography, Salvatore Totino ; editors, Dan Hanely, Mike Hill ; music, Hans Zimmer.
Keywords: Langdon, Robert -- (Fictitious character) -- Drama; Illuminatenorden -- Drama; Signs and symbols -- Italy -- Rome -- Drama; Women scientists -- Italy -- Drama; Terrorism -- Italy -- Drama; Signs and symbols; Terrorism; Women scientists; Vatican City -- Drama; Italy; Italy -- Rome; Video recordings for the hearing impaired; Conspiracy films; Fantasy films; Action and adventure films; Thrillers (Motion pictures); Feature films; Drama